Exploring Local Wisdom Topic Into The English Materials Of Elementary School In Toraja Utara - Matius Tandikombong; Judith Ratu Tandi Arrang; Linerda Tulaktondok (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research aims to find out what types of Toraja local wisdom topics are needed by elementary school students in North Toraja in local content English language teaching materials. This research was conducted in four North Toraja elementary schools, namely SDN 6 Rantepao , SDN 2 Tikala, SDN 7 Tikala and SDN 7 Sesean. The samples from this study were all fourth graders and English teachers who were selected using a total sampling technique. It consisted of 67 students and there were 4 English teachers. The instrument for this research is a questionnaire. The results of this research show that there are 1o local wisdoms topic that need to be included in English teaching materials as Public Speaking subjects, namely: Tourism object, Thanks giving, Funeral ceremony, traditional food, Traditional drink, clothing, social Values, Folklore, arts, Fairytale.